Meta-Sintesis Kualitatif Studi Klinis: Efektivitas Reperfusi Primer dan Farmakoinvasif pada Pasien Stemi - Vera Uliana Simanjuntak; Janet Edrina Ung; Widodo Darmo Sentono (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to compare the effectiveness of two reperfusion strategies in patients with ST-Elevation Myocardial Infarction (STEMI), namely primary percutaneous coronary intervention (PPCI) and the pharmaco-invasive strategy. The method used is a qualitative meta-synthesis with thematic analysis of clinical studies obtained from various scientific databases. The results show that primary reperfusion is superior in reducing mortality and complications when performed within the optimal timeframe (<120 minutes). However, the pharmaco-invasive strategy serves as an effective alternative in areas with limited PCI access, showing comparable clinical outcomes when applied according to time protocols. In conclusion, reperfusion strategy selection must align with the availability of resources and healthcare infrastructure. Keywords: Effectiveness, Meta-Synthesis, Pharmaco-Invasive, Primary Reperfusion, STEMI